2021
DOI: 10.1186/s13046-021-01995-7
|View full text |Cite|
|
Sign up to set email alerts
|

Natural product triptolide induces GSDME-mediated pyroptosis in head and neck cancer through suppressing mitochondrial hexokinase-ΙΙ

Abstract: Background Pyroptosis is a lytic cell death form executed by gasdermins family proteins. Induction of tumor pyroptosis promotes anti-tumor immunity and is a potential cancer treatment strategy. Triptolide (TPL) is a natural product isolated from the traditional Chinese herb which possesses potent anti-tumor activity in human cancers. However, its role in pyroptosis remains to be elucidated. Methods Cell survival was measured by colony formation ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(96 citation statements)
references
References 59 publications
3
92
1
Order By: Relevance
“…1A ). Flow cytometry analysis revealed that IR dose-dependently increased the percentage of dead cells (double positive for 7-AAD and Annexin V, which provides an approximate quantitative estimate of pyroptotic cells) ( 36 ) at 48 h post-irradiation (P<0.05) ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 98%
“…1A ). Flow cytometry analysis revealed that IR dose-dependently increased the percentage of dead cells (double positive for 7-AAD and Annexin V, which provides an approximate quantitative estimate of pyroptotic cells) ( 36 ) at 48 h post-irradiation (P<0.05) ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 98%
“…Pyroptosis-related gene (PRG) signatures can offer insight into prognostic outcomes across a range of cancer types [ 23 , 24 ]. Treatment with TPL can activate GSDME-mediated pyroptosis by inhibiting the expression of HK-II in the mitochondria in HNSCC [ 25 ]. Although PRGs have been shown to have the prognostic value when predicting HNSCC patient outcomes [ 26 ], PRG-mediated immune infiltration and the aberrant changes in the biological behavior of cancer cells remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have identified pyroptosis as a new form of programmed cell death, which plays an essential role in tumor development and treatment mechanisms [ 8 ]. Pyroptosis has been found to play a crucial role in various cancers, such as non-small-cell lung cancer and head and neck cancer [ 34 , 35 ]. Currently, the pyroptosis-related prognostic signature has been constructed in ovarian cancer and gastric cancer, with an excellent prognostic potential [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%